A thermodynamic approach to surface modification of calcium phosphate implants by phosphate evaporation and condensation. Issue 15 (December 2020) - Döbelin, Nicola; Maazouz, Yassine; Heuberger, Roman; Bohner, Marc; Armstrong, Ashley A.; Wagoner Johnson, Amy J.; Wanner, Christoph
Abstract: It has been reported in the literature that thermal treatment of calcium phosphate ceramics chemically alters the surface composition by phosphate evaporation. To predict the compositional changes, we have developed a thermodynamic model for the evaporation of phosphorous species from CPP, TCP, HA, and TetCP. In an open atmosphere, the model predicts the formation of a surface layer consisting of a sequence of increasingly phosphate-depleted phases. In a closed system, the atmosphere reaches equilibrium with a single-phase surface layer. To verify our model, we performed a series of experiments which confirmed the predicted formation of phosphate-depleted surface layers. These experiments further demonstrated that controlled supersaturation of the atmosphere led to formation of a phosphate-enriched surface layer as a result of phosphate condensation. In conclusion, our thermodynamic model is capable of predicting the surface modification by phosphate evaporation and condensation of calcium phosphate phases during high-temperature processing in different environments.